From genes to traits: maximizing phosphorus utilization efficiency in crop plants - Zulfiqar, Sumer; Gu, Ran; Liu, Yan; Zhang, Yaowei (Frontiers in Plant Science, 2025)
Phosphorus (P) is a critical macronutrient for plant growth, but its limited availability requires efficient utilization strategies. The excessive use of P fertilizers leads to low phosphorus utilization efficiency (PUE), causing severe environmental impacts and speeding up the exhaustion of P mineral reserves. Plants respond to inorganic phosphate (Pi) deficiency through complex signaling pathways that trigger changes in gene expression, root architecture, and metabolic pathways to enhance P acquisition and utilization efficiency. By exploring the interplay between genetic regulators and microorganisms, cultivars with superior PUE traits can be developed, which will ensure agricultural resilience and productivity in the face of depleting global P reserves. We highlight the synergistic interaction between genetic regulators and microorganisms to boost PUE as well as recent advancements in unraveling molecular mechanisms governing P homeostasis in plants, emphasizing the urgency to improve plant traits for improved P utilization.